High-strength anti-deformation plastic tray and preparation method thereof
Through a dual dynamic covalent network formed by azide-based crosslinking agent and castor oil crosslinking agent, combined with modified polyethylene and ABS resin and other materials, the problems of insufficient strength and poor deformation resistance of plastic trays are solved, and the comprehensive performance of high strength, deformation resistance and high temperature resistance is achieved.
Patent Information
- Application Number
- CN202510789015.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-13
- Publication Date
- 2025-08-05
AI Technical Summary
The existing plastic pallets are insufficient in strength, difficult to withstand heavy objects pressure, and have poor deformation resistance, which is prone to deformation under high temperature environments, affecting the stability of cargo support and may cause safety hazards.
A double dynamic covalent network is formed by azide-based crosslinking agent and castor oil crosslinking agent. Combined with modified polyethylene, modified ABS resin, silane-modified black talc and PE-g-MA, a high-strength anti-deforming plastic tray is prepared by extrusion blending and hot pressing.
It improves the tensile strength and creep resistance of the plastic pallet, enhances the thermal stability and impact resistance of the material, and achieves comprehensive performance of high strength, deformation and high temperature resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of plastic pallets, in particular to a high-strength deformation-resistant plastic pallet and a preparation method thereof. Background Art
[0002] In the fields of logistics, transportation, and warehousing, plastic pallets have become an indispensable tool for handling and storage due to their light weight, corrosion resistance, and low cost. However, existing plastic pallets have exposed numerous problems in actual use. On the one hand, their lack of strength makes them unable to withstand the pressure of heavy cargo, and they are prone to cracking and damage when carrying heavy objects, which reduces the pallet's service life and increases logistics costs. On the other hand, plastic pallets have poor deformation resistance and are prone to deformation with long-term use, high temperature environments, or improper operation. This not only affects the pallet's support stability for the cargo, but can also lead to uneven stacking of goods and even pose safety risks.
[0003] The rapid development of the logistics industry has placed higher demands on the strength and deformation resistance of plastic pallets. Existing technologies have limitations in addressing these challenges. For example, conventional material formulations struggle to achieve both high strength and good deformation resistance, and traditional manufacturing processes are ineffective in improving the mechanical properties of plastic pallets. Therefore, developing high-strength, deformation-resistant plastic pallets and their manufacturing methods to meet growing logistics needs has become a pressing issue. Summary of the Invention
[0004] The object of the present invention is to provide a high-strength deformation-resistant plastic pallet and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a high-strength, deformation-resistant plastic pallet comprises the following steps: S1: preheating an extruder to 160-165°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5-6 minutes, heating to 214-215°C for reaction for 10-11 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; S2: Add ABS resin, silane-modified black talc powder, and SEBS-g-MA into an extruder, heat and melt blend, and extrude and granulate to obtain modified ABS resin; S3: Add modified polyethylene resin, modified ABS resin, PE-g-MA, castor oil crosslinker, and zinc acetylacetonate into an extruder, heat and melt blend, inject the mixed melt into a mold, and hot-press mold to obtain a high-strength, deformation-resistant plastic pallet.
[0006] Furthermore, during the preparation of the modified polyethylene resin, the amount of the azide cross-linking agent added is 0.5-1 mol% of the molar number of ethylene units in the polyethylene; Furthermore, in the preparation process of the modified ABS resin, the proportions of the components are calculated by mass, including 90-100 parts of ABS resin, 8-12 parts of silane-modified black talc, and 4-8 parts of SEBS-g-MA; Furthermore, the melt blending temperature is 190-245°C; Furthermore, in the preparation process of the high-strength deformation-resistant plastic pallet, the proportions of each component, by mass, include 80-90 parts of modified polyethylene resin, 10-20 parts of modified ABS resin, 8-10 parts of PE-g-MA, 5-10 parts of castor oil crosslinker, and 1-1.2 parts of zinc acetylacetonate.
[0007] Furthermore, the preparation method of the azide cross-linking agent comprises the following steps: adding melamine to tetrahydrofuran, stirring uniformly, adding 1 / 2 mole of N,N-diisopropylethylamine and 1 / 2 mole of N-methylaniline respectively under ice bath conditions, stirring for 1-1.5 hours, adding the remaining N,N-diisopropylethylamine and N-methylaniline, stirring for 15-30 minutes, heating to 30-32° C. and reacting for 17-18 hours, distilling under reduced pressure, adding the product to deionized water, extracting, washing, and drying to obtain an intermediate; The intermediate is added to N-methyl-2-pyrrolidone, sodium azide is added, and the mixture is heated to 100-105°C for reaction for 2.5-3 days. The mixture is cooled to room temperature, and the product is added to deionized water for extraction, washing, and drying to obtain an azido cross-linking agent.
[0008] Furthermore, in the preparation process of the intermediate, the molar ratio of melamine: N,N-diisopropylethylamine: N-methylaniline is 1:2:2; Furthermore, in the preparation process of the azide cross-linking agent, the molar ratio of the intermediate to sodium azide is 1:2.
[0009] Furthermore, the preparation method of the ABS resin includes the following steps: under a nitrogen atmosphere, adding an organic rare earth neodymium phosphate catalyst and diisobutylaluminum chloride to a reaction vessel, heating to 30-35° C. and reacting for 10-15 minutes, adding an ethane solution of sesquiethylaluminum chloride, and aging for 30-35 minutes to obtain a neodymium catalyst; adding butadiene to styrene and stirring evenly, adding the neodymium catalyst, heating to 50-55° C. and reacting for 6-6.5 hours, and adding acidified isopropyl alcohol containing 2,6-di-tert-butyl-4-methylphenol to terminate the reaction to obtain a butadiene prepolymer; Add butadiene prepolymer, acrylonitrile, styrene and ethylbenzene into a reaction vessel, stir evenly, add free radical initiator, react at 75-80℃, 110-115℃ and 125-130℃ for 2-3h, when the conversion rate reaches 30%, heat to 150-155℃ and react for 4-6h, add the product into chloroform, add anhydrous ethanol, and place the precipitate at 50-55℃ and vacuum dry to obtain ABS resin.
[0010] Furthermore, in the preparation process of the neodymium catalyst, the molar ratio of diisobutylaluminum chloride: sesquiethylaluminum chloride: organic rare earth neodymium phosphate catalyst is 10:2:1; in the preparation process of butadiene prepolymer, the mass ratio of butadiene: styrene: neodymium catalyst is (30-40): (170-225): (0.0151-0.0197); Furthermore, during the preparation of the ABS resin, the mass ratio of acrylonitrile:styrene:butadiene prepolymer is (25-40):(45-65):(5-15); Furthermore, the amount of the free radical initiator added is 0.1-0.3 wt % of the total mass of the reaction system.
[0011] Furthermore, the free radical initiator includes any one of benzoyl peroxide and 1,1-bis(tert-butylperoxy)cyclohexane; Furthermore, the preparation method of the silane-modified black talc powder comprises the following steps: adding black talc powder and vinyltriethoxysilane to N,N-dimethylformamide, stirring evenly, heating to 80-100° C., reacting for 30-45 minutes, filtering, washing, and drying to obtain the silane-modified black talc powder; Furthermore, during the preparation of the silane-modified black talc powder, the amount of vinyltriethoxysilane added is 1-2 wt % of the mass of the black talc powder.
[0012] Furthermore, the preparation method of the castor oil cross-linking agent comprises the following steps: adding castor oil and maleic anhydride into a reaction vessel, adding dicumyl peroxide, heating to 120-125° C. for reaction for 5-6 hours, and cooling to room temperature to obtain maleated castor oil; Maleated castor oil and azobisisobutyronitrile are added to tetrahydrofuran, cysteamine is added, and the mixture is heated to 85-90°C for reaction for 48 hours, washed, and vacuum-dried at 80-85°C to obtain aminated castor oil; Aminated castor oil and terephthalaldehyde were added to tetrahydrofuran, stirred at room temperature for 12-16 hours, rotary evaporated, and vacuum dried to obtain castor oil crosslinker.
[0013] Furthermore, in the preparation process of the maleated castor oil, the molar ratio of castor oil: maleic anhydride: dicumyl peroxide is 0.08:0.08:0.001; Furthermore, in the preparation process of the aminated castor oil, the molar ratio of maleated castor oil: azobisisobutyronitrile: cysteamine is 0.0098:0.0074:0.0098; Furthermore, during the preparation of the castor oil cross-linking agent, the molar ratio of aminated castor oil to terephthalaldehyde is 0.0015:0.0075.
[0014] Furthermore, the organic rare earth neodymium phosphate catalyst is prepared according to the prior art CN103694378A.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention utilizes an azide-based crosslinker and a castor oil-based crosslinker to form a dual dynamic covalent network. The azide-based crosslinker generates active nitrene radicals through high-temperature decomposition, which then graft and crosslink with polyethylene chains to form a high-density crosslinking point. Under the catalysis of zinc acetylacetonate, the castor oil crosslinker dynamically exchanges imine and ester bonds, imparting reversible reorganization capabilities to the material. This network effectively disperses stress when subjected to stress, reducing local plastic deformation and thereby improving tensile strength and creep resistance. Silane-modified black talc forms a strong interfacial bond with ABS resin via a silane coupling agent, reducing interfacial defects between the filler and the matrix and enhancing the rigidity and compressive strength of the composite material.
[0016] 2. The polyazane crosslink structure formed by the azide crosslinker and the imine bonds of the castor oil crosslinker reversibly break and reform at high temperatures. The N-N bonds of the polyazane undergo thermomechanically activated exchange at high temperatures, allowing network topology to rearrange without disrupting the overall structure, thereby suppressing high-temperature creep. By controlling the crosslink density (0.5-1 mol% azide crosslinker), the modified polyethylene resin is primarily crosslinked in the amorphous region, preserving the polyethylene's crystalline phase. This maintains the material's high-temperature dimensional stability and provides excellent thermal stability for the plastic pallet.
[0017] 3. The ABS resin in this invention is produced through in-situ bulk polymerization, using high-cis-1,4-polybutadiene (cis degree >96%) as the rubber phase. Its broad molecular weight distribution creates a bimodal rubber particle distribution (large particles induce silver crazing, small particles induce shear yield), synergistically absorbing impact energy. The addition of SEBS-g-MA and PE-g-MA as composite compatibilizers improves the interfacial compatibility between the ABS and polyethylene matrix, reduces phase separation, and further enhances impact resistance.
[0018] 4. By compounding modified polyethylene (high rigidity), modified ABS (high toughness), silane black talc powder (reinforcement), and PE-g-MA (compatibilizer), a multi-scale structure is formed through extrusion blending to achieve a balance of strength, toughness, and thermal stability, achieving the comprehensive properties of high strength, deformation resistance, high temperature resistance, and recyclability. DETAILED DESCRIPTION
[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0020] In the following examples, the polyethylene specification is high-density polyethylene, with a melt flow index of 2.2 g / 10 min, 190 ° C, and a density of 0.94 g / cm 3 The specifications of black talc powder are as follows: particle size of 1250 mesh, SiO2 content of 51.85%, MgO content of 27.74%, CaO content of 4.60%, and Fe2O3 content of 0.25%; castor oil is purchased from Sigma-Aldrich; SEBS-g-MA specification is MA content of 10wt%; PE-g-MA specification is MA content of 8wt%; the remaining raw materials are all commercially available.
[0021] The preparation method of an azide cross-linking agent comprises the following steps: adding 1 mmol of melamine to tetrahydrofuran, stirring uniformly, adding 1 mmol of N,N-diisopropylethylamine and 1 mmol of N-methylaniline respectively under ice bath conditions, stirring for 1 hour, adding 1 mmol of N,N-diisopropylethylamine and 1 mmol of N-methylaniline, stirring for 15 minutes, heating to 30° C. to react for 17 hours, performing reduced pressure distillation, adding the product to deionized water, extracting, washing, and drying to obtain an intermediate; 1 mmol of the intermediate was added to N-methyl-2-pyrrolidone, and 2 mmol of sodium azide was added. The mixture was heated to 100°C for 2.5 days and cooled to room temperature. The product was added to deionized water, extracted, washed, and dried to obtain an azido crosslinker.
[0022] The preparation method of a butadiene prepolymer comprises the following steps: under a nitrogen atmosphere, adding 1 mmol of an organic rare earth neodymium phosphate catalyst and 10 mmol of diisobutylaluminum chloride into a reaction container, heating to 30°C and reacting for 10 minutes, adding 2 mmol of an ethane solution of sesquiethylaluminum chloride, and aging for 30 minutes to obtain a neodymium-based catalyst; adding 30 g of butadiene into 170 g of styrene, stirring evenly, adding 0.0151 g of the neodymium-based catalyst, heating to 50°C and reacting for 6 hours, and adding acidified isopropyl alcohol containing 1 wt% of 2,6-di-tert-butyl-4-methylphenol to terminate the reaction to obtain a butadiene prepolymer.
[0023] The preparation method of silane-modified black talc powder comprises the following steps: adding 100 g of black talc powder and 1 g of vinyltriethoxysilane to N,N-dimethylformamide, stirring evenly, heating to 80° C., reacting for 30 minutes, filtering, washing, and drying to obtain silane-modified black talc powder; The preparation method of a castor oil crosslinker comprises the following steps: adding 0.08 mmol of castor oil and 0.08 mmol of maleic anhydride into a reaction vessel, adding 0.001 mmol of dicumyl peroxide, heating to 120° C. for reaction for 5 hours, and cooling to room temperature to obtain maleated castor oil; 0.0098 mmol of maleated castor oil and 0.0074 mmol of azobisisobutyronitrile were added to tetrahydrofuran, and 0.0098 mmol of cysteamine was added. The mixture was heated to 85°C and reacted for 48 hours. The mixture was washed and dried under vacuum at 80°C to obtain aminated castor oil. 0.0015 mmol of aminated castor oil and 0.0075 mmol of terephthalaldehyde were added to tetrahydrofuran, stirred at room temperature for 12 h, rotary evaporated, and vacuum dried to obtain a castor oil crosslinker.
[0024] Example 1: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.5 mol% of the molar number of ethylene units in the polyethylene; S2: 5 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 90 parts of modified polyethylene resin, 10 parts of modified ABS resin, 8 parts of PE-g-MA, 5 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0025] Example 2: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 1 mol% of the molar number of ethylene units in the polyethylene; The remaining steps are the same as those in Example 1.
[0026] Example 3: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.8 mol% of the molar number of ethylene units in the polyethylene; S2: 15 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. The remaining steps are the same as those in Example 1.
[0027] Example 4: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.8 mol% of the molar number of ethylene units in the polyethylene; S2: 12 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 80 parts of modified polyethylene resin, 20 parts of modified ABS resin, 8 parts of PE-g-MA, 6 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0028] Example 5: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.8 mol% of the molar number of ethylene units in the polyethylene; S2: 12 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 85 parts of modified polyethylene resin, 15 parts of modified ABS resin, 8 parts of PE-g-MA, 6 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0029] Comparative Example 1: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 1.2 mol% of the molar number of ethylene units in the polyethylene; S2: 5 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 90 parts of modified polyethylene resin, 10 parts of modified ABS resin, 8 parts of PE-g-MA, 5 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0030] The remaining steps are the same as those in Example 1.
[0031] Comparative Example 2: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.3 mol% based on the molar number of ethylene units in the polyethylene; S2: 5 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 90 parts of modified polyethylene resin, 10 parts of modified ABS resin, 8 parts of PE-g-MA, 5 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0032] Comparative Example 3: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.5 mol% of the molar number of ethylene units in the polyethylene; S2: 3 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 90 parts of modified polyethylene resin, 10 parts of modified ABS resin, 8 parts of PE-g-MA, 5 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0033] Comparative Example 4: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.5 mol% of the molar number of ethylene units in the polyethylene; S2: 5 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 90 parts of modified polyethylene resin, 8 parts of modified ABS resin, 8 parts of PE-g-MA, 5 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0034] Comparative Example 5: A method for preparing a high-strength, deformation-resistant plastic pallet, comprising the following steps: S1: preheating an extruder to 160°C, adding polyethylene and an azide crosslinker under a nitrogen atmosphere, stirring and mixing for 5 minutes, heating to 214°C for reaction for 10 minutes, extruding and granulating, and cooling to room temperature to obtain a modified polyethylene resin; during the preparation of the modified polyethylene resin, the amount of the azide crosslinker added is 0.5 mol% of the molar number of ethylene units in the polyethylene; S2: 5 g of butadiene prepolymer, 65 g of acrylonitrile, and 35 g of styrene were added to a reaction vessel, ethylbenzene was added to adjust the concentration, and the mixture was stirred evenly. 3 wt% of benzoyl peroxide was added, and the mixture was reacted at 75°C, 110°C, and 125°C for 2 h, respectively. When the conversion rate reached 30%, the mixture was heated to 150°C and reacted for 4 h. The product was added to chloroform, and anhydrous ethanol was added. The precipitate was dried in vacuum at 50°C to obtain ABS resin. S3: 90 parts of ABS resin, 10 parts of silane-modified black talc, and 6 parts of SEBS-g-MA were added to an extruder, heated and melt-blended, and extruded into granules to obtain modified ABS resin; S4: 80 parts of modified polyethylene resin, 10 parts of modified ABS resin, 8 parts of PE-g-MA, 5 parts of castor oil crosslinker, and 1 part of zinc acetylacetonate are added into an extruder, heated and melt-blended, and the mixed melt is injected into a mold and hot-pressed to obtain a high-strength, deformation-resistant plastic pallet.
[0035] Experiment: Mechanical Properties Test: Resin was injection molded into dumbbell-shaped specimens with a parallel section length of 28 mm and a cross-sectional area of 4.0 mm x 2.1 mm. Testing was conducted at room temperature at a rate of 5 mm / min on a universal testing machine according to ASTM D638. The distance between the two fixtures was fixed at 50 mm, and the standard distance (active section) was 20 mm. The test results are shown in Table 1 below.
[0036] Table 1 Mechanical properties test data
[0037] Conclusion: The high-strength deformation-resistant plastic pallets prepared in Examples 1-5 have excellent tensile strength and elongation at break, achieving a balance of strength, toughness, and thermal stability, and are in line with industrial-grade application requirements and sustainable development goals.
[0038] In Comparative Example 1, when the amount of the azide crosslinking agent added was increased to more than 1 mol%, excessive crosslinking resulted in embrittlement of the material, the crosslinking network restricted the slippage of the molecular chains, and the elongation at break decreased.
[0039] In Comparative Example 2, the amount of the azide cross-linking agent added was reduced, the cross-linking density was reduced, the rigidity of the material was weakened, and the tensile strength decreased.
[0040] In Comparative Example 3, the amount of butadiene prepolymer added was reduced, the rigidity was enhanced, the tensile strength was increased, the toughness was decreased, the elongation at break was reduced, and the material was more susceptible to brittle fracture.
[0041] In Comparative Example 4, the addition amount of the modified ABS resin was reduced, resulting in reduced rigidity, tensile strength, toughness, and elongation at break.
[0042] In Comparative Example 5, the amount of modified polyethylene resin added was reduced, the rigidity decreased, the tensile strength decreased, the ethylene rigidity weakened, and the elongation at break increased slightly.
[0043] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.
Claims
1. A method for preparing a high-strength, deformation-resistant plastic pallet, characterized by: The following steps are involved: S1: Preheat the extruder to 160-165°C, add polyethylene and an azide crosslinking agent under a nitrogen atmosphere, stir and mix for 5-6 minutes, heat to 214-215°C, react for 10-11 minutes, extrude and granulate, and cool to room temperature to obtain a modified polyethylene resin; S2: Add ABS resin, silane-modified black talc powder, and SEBS-g-MA into an extruder, heat and melt blend, and extrude and granulate to obtain modified ABS resin; S3: Add modified polyethylene resin, modified ABS resin, PE-g-MA, castor oil crosslinker, and zinc acetylacetonate into an extruder, heat and melt blend, inject the mixed melt into a mold, and hot-press mold to obtain a high-strength, deformation-resistant plastic pallet.
2. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 1, characterized in that: During the preparation of the modified polyethylene resin, the amount of the azide crosslinking agent added is 0.5-1 mol% based on the molar number of ethylene units in the polyethylene; The proportion of each component in the preparation process of the modified ABS resin is calculated by weight, including 90-100 parts of ABS resin, 8-12 parts of silane-modified black talc powder, and 4-8 parts of SEBS-g-MA; In the preparation process of high-strength anti-deformation plastic pallets, the proportion of each component by mass includes 80-90 parts of modified polyethylene resin, 10-20 parts of modified ABS resin, 8-10 parts of PE-g-MA, 5-10 parts of castor oil crosslinker, and 1-1.2 parts of zinc acetylacetonate.
3. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 1, characterized in that: The preparation method of the azide cross-linking agent comprises the following steps: adding melamine to tetrahydrofuran, stirring uniformly, adding 1 / 2 mole of N,N-diisopropylethylamine and 1 / 2 mole of N-methylaniline respectively under ice bath conditions, stirring for 1-1.5 hours, adding the remaining N,N-diisopropylethylamine and N-methylaniline, stirring for 15-30 minutes, heating to 30-32° C. for reaction for 17-18 hours, performing reduced pressure distillation, adding the product to deionized water, extracting, washing, and drying to obtain an intermediate; The intermediate is added to N-methyl-2-pyrrolidone, sodium azide is added, and the mixture is heated to 100-105°C for reaction for 2.5-3 days. The mixture is cooled to room temperature, and the product is added to deionized water for extraction, washing, and drying to obtain an azido cross-linking agent.
4. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 3, characterized in that: During the preparation of the intermediate, the molar ratio of melamine: N,N-diisopropylethylamine: N-methylaniline is 1:2:2; During the preparation of the azido cross-linker, the molar ratio of the intermediate to sodium azide is 1:
2.
5. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 1, characterized in that: The method for preparing ABS resin comprises the following steps: adding an organic rare earth neodymium phosphate catalyst and diisobutylaluminum chloride into a reaction vessel under a nitrogen atmosphere, heating to 30-35° C. and reacting for 10-15 minutes, adding an ethane solution of sesquiethylaluminum chloride, and aging for 30-35 minutes to obtain a neodymium catalyst; adding butadiene to styrene and stirring evenly, adding the neodymium catalyst, heating to 50-55° C. and reacting for 6-6.5 hours, and adding acidified isopropyl alcohol containing 2,6-di-tert-butyl-4-methylphenol to terminate the reaction to obtain a butadiene prepolymer; Add butadiene prepolymer, acrylonitrile, styrene and ethylbenzene into a reaction vessel, stir evenly, add free radical initiator, react at 75-80℃, 110-115℃ and 125-130℃ for 2-3h, when the conversion rate reaches 30%, heat to 150-155℃ and react for 4-6h, add the product into chloroform, add anhydrous ethanol, and place the precipitate at 50-55℃ and vacuum dry to obtain ABS resin.
6. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 5, characterized in that: During the preparation of the neodymium catalyst, the molar ratio of diisobutylaluminum chloride: sesquiethylaluminum chloride: organic rare earth neodymium phosphate catalyst is 10:2:1; during the preparation of butadiene prepolymer, the mass ratio of butadiene: styrene: neodymium catalyst is (30-40): (170-225): (0.0151-0.0197); During the preparation of ABS resin, the mass ratio of acrylonitrile:styrene:butadiene prepolymer is (25-40):(45-65):(5-15); The free radical initiator includes any one of benzoyl peroxide and 1,1-bis(tert-butylperoxy)cyclohexane; the amount of the free radical initiator added is 0.1-0.3 wt% of the total mass of the reaction system.
7. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 1, characterized in that: The preparation method of the silane-modified black talc powder comprises the following steps: adding black talc powder and vinyltriethoxysilane to N,N-dimethylformamide, stirring evenly, heating to 80-100° C., reacting for 30-45 minutes, filtering, washing, and drying to obtain the silane-modified black talc powder; During the preparation of the silane-modified black talc, the amount of vinyltriethoxysilane added is 1-2 wt% of the mass of the black talc.
8. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 1, characterized in that: The preparation method of the castor oil cross-linking agent comprises the following steps: adding castor oil and maleic anhydride into a reaction vessel, adding dicumyl peroxide, heating to 120-125° C. for reaction for 5-6 hours, and cooling to room temperature to obtain maleated castor oil; Maleated castor oil and azobisisobutyronitrile are added to tetrahydrofuran, cysteamine is added, and the mixture is heated to 85-90°C for reaction for 48 hours, washed, and vacuum-dried at 80-85°C to obtain aminated castor oil; Aminated castor oil and terephthalaldehyde were added to tetrahydrofuran, stirred at room temperature for 12-16 hours, rotary evaporated, and vacuum dried to obtain castor oil crosslinker.
9. The method for preparing a high-strength, deformation-resistant plastic pallet according to claim 8, characterized in that: In the preparation of maleated castor oil, the molar ratio of castor oil:maleic anhydride:dicumyl peroxide is 0.08:0.08:0.001; In the preparation of aminated castor oil, the molar ratio of maleated castor oil: azobisisobutyronitrile: cysteamine is 0.0098:0.0074:0.0098; In the preparation process of castor oil cross-linking agent, the molar ratio of aminated castor oil: terephthalaldehyde is 0.0015:0.0075.
10. A high-strength anti-deformation plastic pallet prepared according to the method for preparing a high-strength anti-deformation plastic pallet according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for synthesizing solution-type rare-earth rubber catalyst
CN103694378A